Problematika Bullying Secara Verbal Siswa Kelas IX di MtsS Darul Hadits Kabupaten Pasaman Barat - Elit Purnama Sari; Afrinaldi Afrinaldi; Hamdi Abdul Karim; M. Arif (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This study is motivated by a moral dilemma that arises among students, especially verbal intimidation in the form of words that hurt the victim's heart that can be perceived by the sense of hearing. Bullying is a moral problem that must be addressed in students. Bullying is against moral and religious principles because Islam has instilled good values. Islam strongly recommends mutual respect and appreciation. With the existence of Islamic religious education teachers emphasizing the importance of Islamic teaching in transmitting values and reducing social violence in madrasas. For this reason, the problem of bullying is so complex and urgent to study. Therefore, to find out how teachers' efforts to deal with bullying behavior that occurs, it is necessary to conduct research on handling bullying. So that it can be used as a reference or reference to prevent and deal with problems such as bullying. The purpose of this study was to identify the causes, forms, efforts of PAI teachers or school teachers' solutions in dealing with verbal bullying. This research is a type of field research, namely qualitative research. In this study, data were collected through interviews, observation and documentation. Therefore, the task of the teacher is as a facilitator and mediator for their students, it is hoped that the presence of the Islamic Religious Education Teacher will be able to influence the attitudes and behavior of students to avoid violence in schools such as bullying.